2004
DOI: 10.1149/1.1633765
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Mechanisms of Ethylene, Propylene, and Vinylethylene Carbonates

Abstract: Quantum chemical methods have been used to study reduction mechanisms of ethylene carbonate ͑EC͒, propylene carbonate ͑PC͒, and vinylethylene carbonate ͑VEC͒, in electrolyte solutions. The feasibility of direct two-electron reduction of these species was assessed, and no barrier to reaction was found for the formation of Li 2 CO 3 and 1,4-butadiene from VEC. In contrast EC and PC have barriers to reaction on the order of 0.5 eV. The ready formation of Li 2 CO 3 when VEC is reduced may explain why it acts as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
201
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(206 citation statements)
references
References 22 publications
2
201
0
Order By: Relevance
“…[8][9][10][11][12][13] One may argue that its ubiquity and critical role make EC in LIB the battery equivalent of the H 2 O molecule in biology, geochemistry, and many solid-liquid interfacial science disciplines. The present work is indeed modeled after theoretical studies on water-on-mineral surfaces.…”
Section: -3mentioning
confidence: 99%
“…[8][9][10][11][12][13] One may argue that its ubiquity and critical role make EC in LIB the battery equivalent of the H 2 O molecule in biology, geochemistry, and many solid-liquid interfacial science disciplines. The present work is indeed modeled after theoretical studies on water-on-mineral surfaces.…”
Section: -3mentioning
confidence: 99%
“…It has also been shown that adding a few weight-percent of VEC to PC-based electrolytes significantly improves their performance. 125 Calculations in this work showed VEC underwent direct two-electron reduction more readily than EC and PC and thus should react more readily to form the passivating Li 2 CO 3 . Lucht et al 126 have investigated electrolyte stabilizing additives that reduce species known to attack the SEI layer, namely dimethyl acetamide and N-methyl-2-pyrrolidone (NMP).…”
Section: Lithium Alloy Anodesmentioning
confidence: 72%
“…Extensive work has gone into characterizing and modeling the effects of these additives. 124,125,126,127,128 Work by Aurbach et al 129 showed that VC polymerizes on the lithiated graphite surfaces, forming poly alkyl Li-carbonate species that suppress both solvent and salt anion reduction. Shima et al 130 have shown increased thermal stability of electrolytes with this additive while Ota et al 121 showed enhanced thermal stability of the VC-derived SEI coating on the exposed anode surfaces.…”
Section: Lithium Alloy Anodesmentioning
confidence: 99%
“…Although there are numerous compounds in the patent literature that are claimed to have such properties, only a few have been studied and discussed in publications. Examples are ethylene sulfite [4], and the unsaturated carbonates vinylene carbonate (VC) [5][6][7][8][9][10] and vinyl ethylene carbonate (VEC) [11][12]. The electrochemical reduction of both VC and VEC has been studied in some detail, including quantum chemical calculations of the energetics that identified the most probable reaction pathway [13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [11] proposed that VEC was more stable than VC and demonstrated that it functioned successfully as a film forming additive in PC based electrolyte. Vollmer et al [12] examined the reduction chemistry of EC, PC and VEC using quantum chemical Density Functional Theory and concluded that the reduction potential of VEC is ca. + 1 V 3 more positive than that of EC or PC, indicating that VEC would probably be preferentially reduced to form a passivating film.…”
Section: Introductionmentioning
confidence: 99%